2022
DOI: 10.1177/17562848221140657
|View full text |Cite
|
Sign up to set email alerts
|

Update on the role of elastography in liver disease

Abstract: The diagnosis of liver fibrosis and the assessment of its severity are important to provide appropriate management, to determine the prognosis or the need for surveillance. Currently, for fibrosis staging, liver stiffness measurement (LSM) with the shear wave elastography (SWE) techniques is considered a reliable substitute for liver biopsy in several clinical scenarios. Nonetheless, it should be emphasized that stiffness value is a biomarker of diffuse liver disease that must be interpreted taking into consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 78 publications
(201 reference statements)
1
13
0
Order By: Relevance
“…In a recent prospective study by Yoo et al [22] assessing interobserver-variability of SWE measurements in 53 patients with chronic liver disease, the authors found an excellent inter-and intra-observer agreement. Similar results can be found in the literature in studies in patients with chronic liver disease as well as in both elasticity phantoms and healthy individuals [23][24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…In a recent prospective study by Yoo et al [22] assessing interobserver-variability of SWE measurements in 53 patients with chronic liver disease, the authors found an excellent inter-and intra-observer agreement. Similar results can be found in the literature in studies in patients with chronic liver disease as well as in both elasticity phantoms and healthy individuals [23][24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…Agreement between transient elastography and 2D-SWE might be poor in HIV mono-infected people due to the presence of confounding factors, such as steatosis or hepatic necro-inflammatory activity associated with a low prevalence of fibrosis, known as spectrum bias [15]. The impact of the spectrum bias and potential confounding factors in staging liver fibrosis by non-invasive methods was previously reported [21,27]. Additionally, metabolic features or liver steatosis are highly frequent in people living with HIV mono-infection under antiretroviral therapy [28].…”
Section: Discussionmentioning
confidence: 99%
“…2 It is also used in treatment monitoring 3 as well as image-guided therapy. 4 By evaluating tissue elasticity, elastography techniques enable the diagnosis of lung diseases like pulmonary fibrosis, 5,6 pulmonary edema, 7 and emphysema, 8 as well as liver conditions such as fibrosis, 9 cirrhosis, 10 and hepatic tumors. 11 In renal disease, elastography aids in the early detection of subclinical renal fibrosis, 12 a major risk factor for chronic kidney disease, offering a valuable tool for preventive intervention.…”
Section: Introductionmentioning
confidence: 99%